IMPLEMENTASI QIRAAT SAB’AH DALAM QIRAAT ALQURAN - fauziah, cut (At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2019)
This article discused about Qiraat Alquran from the narrator side to determine is this Qiraat accepted or rejected. In Quranic Sciences it is know as Qiraah Sab?ah, there are 3 requirements must be fulfilled by Qiraat in order tobe acccepted they are : its sanad must be mutawatir, which is accepted by the trusted teachers, has no problem inside, and has continuation link to prophet Muhammad saw., it also has to be famous among  the Qiraat members, and compatible with arabic grammar. Qiraat  Sab?ah is the Qiraah which has perfect continuation, which tranferred from  prophet  Muhammad saw. by a group of people who disagree to prevaricate, Qiraat Mutawatir is alegitimate and official qiraah from Alquran it is allowed to read during prayer or outside prayer using  these rules of Qiraat.